Context and Implications Document for: The influence of socio‐economic background and gender on PISA attainment in the United Kingdom: A systematic review. Issue 1 (21st June 2019) - Early, Erin; Miller, Sarah; Dunne, Laura; Thurston, Allen; Filiz, Mehmet
Abstract : This guide accompanies the following article: Early, E., Miller, S., Dunne, L., Thurston, A. & Filiz, M. (2019) The influence of socio‐economic background and gender on PISA attainment in the United Kingdom: A systematic review, Review of Education, https://doi.org/10.1002/rev3.3175 .